Effects of Analgesia-Sedation on the Relationship Between NKG2D and Its Ligands MICA, MICB - Akyol, Sibel; Türeci, Ercan; Çetintaş, Semih Can; Hancı, Murat (Cerrahpaşa Medical Journal, 2021)
Objective: This study aims to investigate the influence of analgesia-sedation on the expression of natural killer cells, and the NKG2D receptor and MICA/MICB ligand changes in patients who had cerebral digital subtraction angiography for either the diagnosis or treatment of intracranial vascular pathologies. Methods: Forty-one male patients who were admitted for cerebral digital subtraction angiography were included in this study. The patients were divided into 2 groups: group I (n = 7) included patients who did not receive anesthesia, and group II (n = 34) comprised those who received anesthesia. For the molecules, the venous blood samples were collected from every patient before and after cerebral digital subtraction angiography. Results: In group I, the natural killer cells, the NKG2D receptor, the MICA/MICB ligands, and the CD3 and CD8 cytokines were increased significantly after the DSA, but the CD16+56+ cells and the MHC-I molecules showed no statistically significant difference. In group II, the natural killer cells, CD16+56+ cells and the MICA/MICB levels did not show significant difference. On the other hand, the NKG2D, MHC-I, and the CD8+ and CD3+ cell levels increased significantly after the digital subtraction angiography. Comparing the group I and II after the digital subtraction angiography showed no significant difference regarding CD16+56+ and NKG2D. The natural killer (CD56+), and MICA/MICB levels decreased, and the MHC-I, CD8+, and CD3+ levels increased significantly in group II. Conclusion: Analgesia-sedation combined with surgical stress in digital subtraction angiography causes some alterations in the immune status of patients. More data will enable us to administer the appropriate agents in order to strengthen their immune status during the preoperative period for decreasing the morbidity and/or mortality rate. Cite this article as: Akyol S, Türeci E, Çetintaş SC, Hancı M. Effects of Analgesia-Sedation on the Relationship Between NKG2D and Its Ligands MICA, MICB. Cerrahpaşa Med J. 2021;45(2):95-100.